2022
DOI: 10.9744/jak.24.1.46-56
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Readability of Annual Reports and Value Relevance of Financial Information on Agency Costs with Analyst Coverage as Moderating Variable

Abstract: This study aims to determine the effect of readability based on the length of the annual report and the value relevance of the financial information on agency costs. The sample used in this study were 263 firm-year from Kompas100 index. Data were analyzed using multiple linear regression method. The result of this study indicate that the higher the number of pages, words and characters, which reflects the poor readability of the annual report, has a negative effect on the asset turnover ratio, which is an inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The study aims to address the potential problems associated with controlling for endogeneity by utilizing the Coarsened Exact Matching (CEM) approach. CEM serves as an alternative method to address the issue of independent selection and focuses on observed variables that have the potential to influence the results in the regression analysis, as suggested by [54,57]. 6, thereby supporting the hypotheses put forth in the study.…”
Section: Endogeneity Issuementioning
confidence: 82%
See 1 more Smart Citation
“…The study aims to address the potential problems associated with controlling for endogeneity by utilizing the Coarsened Exact Matching (CEM) approach. CEM serves as an alternative method to address the issue of independent selection and focuses on observed variables that have the potential to influence the results in the regression analysis, as suggested by [54,57]. 6, thereby supporting the hypotheses put forth in the study.…”
Section: Endogeneity Issuementioning
confidence: 82%
“…In response, the government implemented various preventive measures across sectors. One significant consequence of the Pandemic has been the increased uncertainty surrounding economic policies, prompting firms to adopt a more cautious approach to managing their cash holdings [11,53,54]. Given the prevailing uncertain economic conditions, it is likely that firms will choose to bolster their cash reserves as a precautionary measure [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, El-Din et al ( 2022) reported that more readable (less complex) annual reports increase financial analysts' earnings forecasting accuracy, improve stock liquidity, and enhance investors' valuation of a company, which reduces a company's costs and improves its profitability. A recent study by Soesanto and Wijaya (2022) examined the moderating effect of the value relevance of financial information and analyst coverage on the relationship between annual report readability and agency costs. They depended on a sample of 263 Indonesian companies listed on the Kompas 100 index during the period 2016-2019.…”
Section: Agency Costs Complexity Of the Annual Report And Firm Profit...mentioning
confidence: 99%